Economic analysis of crop livestock integration in oil palm plantation / Muhamad Iqbal Izzat Muhamad Rakman - Muhamad Rakman, Muhamad Iqbal Izzat (Faculty of Plantation and Agrotechnology, 2019)
Livestock integration in oil palm industry has been one of the trend nowadays in Malaysia. Livestock integration is one of the application of mixed farming or integration farming that combining two or more commodity in one area of agriculture. This study is focusing on the economic analysis of crop livestock integration in oil palm plantation. The objective of this research is to study the economic analysis of different livestock integration system for different oil palm plantation affecting the production of yield. It also help to determine which practices is the most economical for livestock integration to be applied in the plantation. The location of this research study was done at LKPP Pulau Manis at Pahang and Jaya Baru plantation in Perak. The method of data collection are by interview or face to face with the responsible person and secondary data. Next, the data have been analyses by using descriptive analysis, benefit cost ratio and independent sample T- test. Two type of software to analyses the data have been use such as Microsoft Excel and Statistical Package for Social Science (SPSS). As a results, it was shown that livestock integration system applied by LKPP is more economical compare to the Jaya Baru estate. From the t-test analysis, it was prove statistically that the oil palm FFB production for LKPP Pulau Manis is significantly higher based on the p-value is 0.000. This is the effects of livestock integration system applied. As a recommendation for the livestock integration plantations, it would be significantly recommended for the management to apply the systems done by LKPP Pulau Manis in their practices.